Myelopathy in a child after SARS-COV-2 infection: a case report from Sumy, Ukraine - Smiyan, O.; Horbas, V.; Shevchenko, N.; Buhaienko, V.; Lendych, Yu.; Marchenko, O.; Vasilyeva, O.; Reznychenko, Yu.; Vysotsky, I.; Сміян, О.; Горбась, В.; Шевченко, Н.; et al. (My University, 2024)
Introduction. The post-acute course in children in 22% of cases may have signs of nervous system damage. Common symptoms are headache, cognitive problems, anosmia, seizures, Guillain-Barré syndrome, demyelinating syndrome and autoimmune encephalitis, acute disseminated encephalomyelitis, posterior reversible encephalopathy syndrome, viral encephalitis, and gait difficulties. The study aims to describe a rare clinical case of post-COVID syndrome in children with nervous system lesions. Materials and methods. A 9-year-old girl with myelopathy, lower spastic paraparesis, post-COVID syndrome, who was treated in the neurological department of the St. Zinaida Children's Clinical Hospital of the City of Sumy, was studied. The following research methods were carried out for differential diagnosis and confirmation of the disease: clinical blood and urine tests, cerebrospinal fluid analysis, virological examinations (adenovirus, enterovirus, cytomegalovirus, herpes simplex virus types 1, 2, SARS-CoV-2), magnetic resonance imaging of the brain and spine, electroneuromyography. Вступ. Постковідний перебіг у дітей в 22% випадків може мати ознаки ураження нервової системи. Поширеними симптомами частіше можуть бути такі, як головний біль, когнітивні проблеми, аносмія, судоми, синдром Гійєна-Барре, демієлінізаційний синдром і аутоімунний енцефаліт, гострий дисемінований енцефаломієліт, синдром задньої оборотної енцефалопатії, вірусний енцефаліт і труднощі з ходою, такі як м'язова слабкість та атрофія м'язів. Мета роботи. описати рідкісний клінічний випадок ускладнення коронавірусної інфекції у дитини з ураженням нервової системи. Матеріали та методи. Під спостереженням дівчинка 9 років з постковідним синдромом, нижнім спастичним парапарезом мієлопатією, що знаходилась на лікуванні у неврологічному відділенні «Дитяча клінічна лікарня Святої Зінаїди» Сумської міської ради. Для диференційної діагностики та підтвердження захворювання були проведені наступні методи дослідження: клінічний аналіз крові та сечі, аналіз спинномозкової рідини, вірусологічні обстеження (аденовірус, ентеровірус, цитомегаловірус, вірус простого герпесу 1, 2 типів, вірус Епштейна-Барра, SARS-CoV-2), МРТ головного мозку та хребтового стовпа, електронейроміографія.
Мієлопатія у дитини після інфекції SARS-COV-2: клінічний випадок, м. Суми, Україна
Keywords: clinical case; children; post-covid syndrome; nervous system; lower spastic paraparesis; myelopathy; клінічний випадок; діти; постковідний синдром; нервова система; нижній спастичний парапарез; мієлопатія